Impact of the Establishment of a Specialty Hernia Referral Center. (December 2014) - Williams, Kristopher B.; Belyansky, Igor; Dacey, Kristian T.; Yurko, Yuliya; Augenstein, Vedra A.; Lincourt, Amy E.; Horton, James; Kercher, Kent W.; Heniford, B. Todd
Background . Creating a surgical specialty referral center requires a strong interest, expertise, and a market demand in that particular field, as well as some form of promotion. In 2004, we established a tertiary hernia referral center. Our goal in this study was to examine its impact on institutional volume and economics. Materials and methods . The database of all hernia repairs (2004-2011) was reviewed comparing hernia repair type and volume and center financial performance. The ventral hernia repair (VHR) patient subset was further analyzed with particular attention paid to previous repairs, comorbidities, referral patterns, and the concomitant involvement of plastic surgery. Results . From 2004 to 2011, 4927 hernia repairs were performed: 39.3% inguinal, 35.5% ventral or incisional, 16.2% umbilical, 5.8% diaphragmatic, 1.6% femoral, and 1.5% other. Annual billing increased yearly from 7% to 85% and averaged 37% per year. Comparing 2004 with 2011, procedural volume increased 234%, and billing increased 713%. During that period, there was a 2.5-fold increase in open VHRs, and plastic surgeon involvement increased almost 8-fold, ( P = .004). In 2005, 51 VHR patients had a previous repair, 27.0% with mesh, versus 114 previous VHR in 2011, 58.3% with mesh ( P < .0001). For VHR, in-state referrals from 2004 to 2011 increased 340% while out-of-state referrals jumped 580%. In 2011, 21% of all patients had more than 4 comorbidities, significantly increased from 2004 ( P = .02). Conclusion . The establishment of a tertiary, regional referral center for hernia repair has led to a substantial increase in surgical volume, complexity, referral geography, and financial benefit to the institution.